The Party for 1924. (1924)
1 photograph : sepia toned 8 x 13.5 cm Samuel F. Milley, William Robertson Warren, Donnelly, Robert George Rendell posing for a photograph near the Grand River. Title from album caption. Samuel F. Milley (1867-1939) was born in St. John's in 1867. Milley was a prominent dry goods merchant in St. John's from 1890's and was a member of the Legisaltive Council for more than 30 years. Milley died in Montreal on February 12, 1939. William Robertson Warren (1879-1927), son of William Henry and Jessie (Harvey) Warren, was born in St. John's in 1879. He began his political career in 1903, and became Prime Minister of Newfoundland from July 1923 - April 1924. Warren died suddenly on December 31, 1927. Robert George Rendell (1857?- 1928) was born in St. John's, son of Catharine (Norris) and Stephen Randell. Married Helen Mackay. In 1913, acting as administrator of the C.F. Bennett mining estate, he and mine manager J.M. Jackman acquired right to operate the Tilt Cove Mine. Rendell was colonel of the Newfoundland Church Lads' Brigade from 1904 to 1918 and was a member of the Imperial Red Cross Committee. Rendell died in 1928. Samuel J. Foote (1873-1936) was born in Grand Bank in 1873. Foote was called to the Newfoundland Bar in 1899 and went to practice with Sir James Winter. Foote entered into politics in 1904. Foote died on December 8, 1936.John Cormier sold the house and land at Forks Pool on the Grand River, Codroy, July 11, 1914 to the FOMOWA Fishing Club. Good An album containing 323 black and white photographs and 25 pages of text, covering the years 1914 to 1937 of the FOMOWA Fishing Club on the Grand Codroy River on the west coast of Newfoundland. The album's images have been digitized as separate items.